Lithuanian children – deportees of 1948 - Burauskaitė, Birutė (Genocidas ir rezistencija, 2025)
The aim of this presentation is to analyse in more detail the dynamics of child mortality in exile. It is known from the testimonies of many deportees that the first years of life in exile were the most difficult and brought the most painful losses, but it was only after the creation of a database of repressed persons that it became possible to establish the true extent of the deaths caused by the mass deportation of 1948, based not only on numbers but also on the personal data of each victim of repression.